impact of broken home, cause of The Impact of Broken Homes on Adolescent Social Behavior: A Case Study in Dusun Bagik Dopol, Desa Mertak Tombok : The Impact of Broken Homes on Adolescent Social Behavior: A Case Study in Dusun Bagik Dopol, Desa Mertak Tombok - Syuhada, Novita (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
This study examines the impact of broken homes on the social behavior of adolescents in Bagik Dopol Hamlet, Mertak Tombok Village, Praya District, Central Lombok Regency. The method used in this research is a qualitative method with a case study approach. Data collection using semi-structured interview methods, observation and documentation on adolescents who come from broken home family environments. The subjects in this study amounted to four teenagers. Data were analyzed using the Miles and Huberman model which involves five stages, namely data collection, data reduction, data display, conclusions, and triangulation. The result of this study is that adolescents who experience broken homes in Bagik Dopol Hamlet occur because their parents are divorced. The divorce of his parents was caused by economic factors, closed communication and the existence of a third person / affair. Most of the subjects in this study were able to adapt and interact well with the people around them. Having a good relationship with parents even though they do not live together. Three of the four subjects had positive behaviors and one of the four subjects had negative behaviors such as consuming alcoholic beverages and skipping classes.